Robbins, the Great Depression - Mitchell, Wesley C. (Quarterly Journal of Economics, 1935)
Journal Article Robbins, The Great Depression Get access Wesley C. Mitchell Wesley C. Mitchell Columbia University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 49, Issue 3, May 1935, Pages 503–507, https://doi.org/10.2307/1883866 Published: 01 May 1935